Comparison of Fungal Community in Black Pepper-Vanilla and Vanilla Monoculture Systems Associated with Vanilla Fusarium Wilt Disease - Xiong, Wu; Zhao, Qingyun; Xue, Chao; Xun, Weibing; Zhao, Jun; Wu, Huasong; Li, Rong; Shen, Qirong (Frontiers in Microbiology, 2016)
Long-term vanilla monocropping often results in the occurrence of vanilla Fusarium wilt disease, seriously affecting its production all over the world. In the present study, vanilla exhibited significantly less Fusarium wilt disease in the soil of a long-term continuously cropped black pepper orchard. The entire fungal communities of bulk and rhizosphere soils between the black pepper-vanilla system (i.e., vanilla cropped in the soil of a continuously cropped black pepper orchard) and vanilla monoculture system were compared through the deep pyrosequencing. The results showed that the black pepper-vanilla system revealed a significantly higher fungal diversity than the vanilla monoculture system in both bulk and rhizosphere soils. The UniFrac-weighted PCoA analysis revealed significant differences in bulk soil fungal community structures between the two cropping systems, and fungal community structures were seriously affected by the vanilla root system. In summary, the black pepper-vanilla system harboured a lower abundance of F. oxysporum in the vanilla rhizosphere soil and increased the putatively plant-beneficial fungal groups such as Trichoderma and Penicillium genus, which could explain the healthy growth of vanilla in the soil of the long-term continuously cropped black pepper field. Thus, cropping vanilla in the soil of continuously cropped black pepper fields for maintaining the vanilla industry is executable and meaningful as an agro-ecological system.